Local immunity in ulcerative colitis: evidence for defective secretory IgA production. Issue 8 (August 1988) - Badr-el-Din, S; Trejdosiewicz, L K; Heatley, R V; Losowsky, M S
Abstract : To investigate local humoral immunity in ulcerative colitis (UC), immunoglobulin (Ig) contents and net Ig production in vitro was assessed using organ cultures of colonic biopsies from 21 patients with quiescent disease and 11 controls. Ig was estimated by enzyme linked immunoassay (ELISA) for IgA, secretory IgA (sIgA), IgM, and IgG. In parallel, numbers of IgA plasma cells were estimated by indirect immunoperoxidase staining of tissue sections for IgA. IgA was the dominant Ig isotype found pre-existing in colonic mucosae, and secreted in vitro. In UC patients, preformed tissue IgA and IgA produced in vitro were significantly increased compared with controls. There was no concomitant increase in amounts of sIgA synthesised in culture, however, although numbers of IgA plasma cells were increased in UC patients by an amount comparable with the increased in vitro IgA production. These results directly show a dysfunction of transepithelial IgA secretion in quiescent ulcerative colitis. Despite a significantly raised concentration of tissue IgG in UC patients, little was produced in vitro in patient and control groups alike, suggesting that mucosal IgG was serum derived, and not linked to local IgA production.